Corporate tax minimization and stock price reactions - Kay Blaufus; Axel Möhlmann; Alexander Schwäbe (Arbeitskreis Quantitative Steuerlehre (arqus), 2016)
Tax minimization strategies may lead to significant tax savings, which could, in turn, increase firm value. However, such strategies are also associated with significant costs, such as expected penalties and planning, agency, and reputation costs. The overall impact of firms' tax minimization strategies on firm value is, therefore, unclear. To investigate whether corporate tax minimization increases firm value, we analyze the stock price reaction to news concerning corporate tax avoidance or evasion. Our hand-collected dataset includes 139 tax news items regarding listed German firms over the period from 2003 to 2014. In contrast to previous research, we explicitly distinguish between news about legal tax minimization (tax avoidance) and illegal tax minimization (tax evasion). We show that stock market responses differ significantly between news items concerning legal and illegal activities. While we find negative abnormal returns for tax evasion news, we find positive abnormal returns for tax avoidance news. Our results do not indicate any reputation effect of legal tax minimization. Conversely, the positive market reaction to tax avoidance news is associated with firms that face high reputation risk.
Keywords: G14; G30; H25; H26; 330; tax avoidance; tax evasion; tax aggressiveness; tax risk; market reaction; event study